2011
DOI: 10.1371/journal.pone.0019314
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Monitoring of Fecal Steroid Hormones in Female Snow Leopards (Panthera uncia) during Pregnancy or Pseudopregnancy

Abstract: Knowledge of the basic reproductive physiology of snow leopards is required urgently in order to develop a suitable management conditions under captivity. In this study, the long-term monitoring of concentrations of three steroid hormones in fecal matter of three female snow leopards was performed using enzyme immunoassays: (1) estradiol-17β, (2) progesterone and (3) cortisol metabolite. Two of the female animals were housed with a male during the winter breeding season, and copulated around the day the estrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…This could be due to the female's reproductive hormone cycles since cyclic fluctuations of oestrogen and progesterone could influence the expression of FCM [38]. The reproductive and stress hormonal axes are tightly linked and the variation in corticosteroids could reflect the different phases of reproduction such as oestrous, gestation, lactation [21]. Most likely, it is the increased metabolic demands associated with reproduction that could drive the variation in FCM concentrations in females since cortisol is a metabolic hormone [48].…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the female's reproductive hormone cycles since cyclic fluctuations of oestrogen and progesterone could influence the expression of FCM [38]. The reproductive and stress hormonal axes are tightly linked and the variation in corticosteroids could reflect the different phases of reproduction such as oestrous, gestation, lactation [21]. Most likely, it is the increased metabolic demands associated with reproduction that could drive the variation in FCM concentrations in females since cortisol is a metabolic hormone [48].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ELISA has more advantages for the analysis of many samples. In the last two decades, ELISAs have been developed for monitoring fecal steroid metabolites in a variety of animals [9,7,10,15,[17][18][19]22,[29][30][31][32]. Studies have also indicated that different species excrete different metabolites of the same parent steroid compound due to changes in metabolism and excretion pattern [11,26].…”
Section: Introductionmentioning
confidence: 99%
“…Separated blood serum samples were stored frozen (−20°C) until enzyme immunoassay (EIA) test on P 4 was performed according to the modified method described by Kinoshita et al. (), without dilution.…”
Section: Methodsmentioning
confidence: 99%